Exercise Video Games and Exercise Self-Efficacy in Children - Hildemar Dos Santos MD, DrPH; Margaret Dinhluu Bredehoft MPH, DrPH; Frecia M. Gonzalez MPH; Susanne Montgomery PhD (SAGE Publishing, 2016)
The aim of this article was to investigate the use of exergaming in promoting exercise behavior among children and to examine the impact of the intervention on participants' exercise self-efficacy, in addition to assessing physiological changes. A sample of 55 children enrolled in the Family Fit program, where participants were categorized into 2 groups: healthy weight and overweight. Measures were taken at baseline, after the 7-week program, at the 12-week follow-up, and at the 24-month follow-up. Positive changes in exercise self-efficacy were significant for the overweight group, while the healthy weight group maintained their exercise self-efficacy. At the 24-month follow-up, 97% children reported being interested in participating in a future fitness program, and 96% children who did not play sports before the intervention started practicing sports. Exercise self-efficacy is a predictor of physical activity, and incorporating exergaming in a structured program may lead to increased self-efficacy in participants.